Iowa Birdline update, January 2, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for January 2, 1994. Highlights include Gulls, a Gyrfalcon and a Long-tailed Duck. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed